Simple, Swift, and Low Cost Judiciary in Handling Environmental Crimes by Corporations through Deferred Prosecution Agreement - Rosnawati, Emy; Warka, Made; Setyorini, Erny Herlin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Indonesia's criminal justice system aspires to uphold the principles of simplicity, swiftness, and cost-efficiency. Specific Background: However, these ideals remain inadequately realized, particularly in addressing environmental crimes perpetrated by corporations—cases often burdened by protracted processes and limited effectiveness in restoring state losses. Knowledge Gap: Conventional legal approaches have failed to achieve significant restitution, signaling a need for alternative mechanisms. Aims: This study examines the potential application of the Deferred Prosecution Agreement (DPA) framework as a tool to actualize a more efficient judiciary in prosecuting corporate environmental offenses. Results: Using a normative juridical method with statutory and comparative approaches, the study finds that the DPA offers a concrete, legally feasible means of pursuing compensation while streamlining judicial procedures. Novelty: The research introduces the concept of DPA into Indonesia’s legal discourse as an innovative, non-traditional solution for environmental crime cases involving corporate actors. Implications: The adoption of DPA mechanisms, accompanied by normative and institutional adjustments, could significantly enhance Indonesia's judicial efficiency and environmental accountability frameworks. Highlights: Promotes judicial principles of simplicity, speed, and cost-efficiency. Offers innovative restitution for environmental damage by corporations. Requires legal and institutional adaptation for implementation in Indonesia. Keywords: Expedited Justice, Simplicity, Low-Cost Proceedings, Environmental Pollution, Deferred Prosecution Agreement